Chapter Mapping of the risk of coastal erosion for two case studies: Pianosa island (Tuscany) and Piscinas (Sardinia) - Ghirardi, Nicola (Proceedings e report, 2020)
This study focuses on the use of remote sensing to generate coastal erosion risk maps for Pianosa Island (Tuscany) and Piscinas dune system (Sardinia). The method made use of both ancillary and satellite data (Sentinel-2), in addition to SAR images (COSMO SkyMed and Sentinel-1B). TOA radiance products were atmospherically corrected and processed using Sen2Coral and BOMBER in order to map different marine substrates and bathymetry. The coastal erosion risk maps have been generated based on these output and the results confirm that the coasts of these sites don't have coastal erosion problems.